A therapeutic effect of Nigella sativa extract on female Wistar rats vulvovaginal candidiasis model - Muhammad Rusda; Muhammad Fidel Ganis Siregar; Aznan Lelo; Syafruddin Ilyas; Ratna Akbari Ganie; Yusuf Effendi; Poppy Anjelisa Zaitun Hasibuan; Raden Roro Lia Iswara (Medicinski glasnik, 2020)
Aim: Vulvovaginal candidiasis (VVC) is a disease mostly caused by Candida albicans and affects the quality of life of women especially in the form of chronic recurrent vulvovaginal candidiasis (RVVC). Nigella sativa is known to have several effects such as antimicrobial, anti-inflammatory, immune stimulation and anticancer properties. The aim of this study was to evaluate the effect of Nigella sativa on vulvovaginal candidiasis. Methods: This study is a true experimental design, we used 28 Wistar strain rats divided into 4 groups, all groups were conditioned in a pseudoestrus state. Candida albicans was inoculated into the rats' vagina for 3 consecutive days. All groups were observed every 24 hours, 48 hours and 72 hours to evaluate the number of Candida albicans colonies, IgG and IgM anti Candida. Results: After administration of intervention, there was a significant difference in the amount of fungal colonization after the treatment in each group (p<0.001). There was no significant difference in the effectiveness of Nigella sativa and fluconazole in supressing Candida albicans colonies after 72 hours (p=0.101). The administration of Nigella sativa showed a significant difference in the increase in IgM levels compared to the others group (p<0.001), while the IgG level did not show a significant difference (p=0.423). Conclusion: Nigella sativa provides a therapeutic effect by decreasing the number of fungal colonies and increasing IgM levels.
Keywords: Candida albicans; fungal inoculation; pseudoestrus